Zero-quantum frequency-selective recoupling of homonuclear dipole-dipole interactions in solid state nuclear magnetic resonance - Hu, Kan-Nian (U.S. Government, 2009)
We describe a method for measuring magnetic dipole-dipole interactions, and hence distances, between pairs of like nuclear spins in a many-spin system under magic-angle spinning (MAS). This method employs a homonuclear dipolar recoupling sequence that creates an average dipole-dipole coupling Hamiltonian under MAS with full zero-quantum symmetry, including both secular and flip-flop terms. Flip-flop terms are then attenuated by inserting rotor-synchronized periods of chemical shift evolution between recoupling blocks, leaving an effective Hamiltonian that contains only secular terms to a good approximation. Couplings between specific pairs of nuclear spins can then be selected with frequency-selective π pulses. We demonstrate this technique, which we call zero-quantum shift evolution assisted homonuclear recoupling, in a series of one-dimensional and two-dimensional (13)C NMR experiments at 17.6 T and 40.00 kHz MAS frequency on uniformly (13)C-labeled L-threonine powder and on the helix-forming peptide MB(i+4)EK, synthesized with a pair of uniformly (13)C-labeled L-alanine residues. Experimental demonstrations include measurements of distances between (13)C sites that are separated by three bonds, placing quantitative constraints on both sidechain and backbone torsion angles in polypeptides.